DEARYLATION IN THE INTERACTIONS BETWEEN (Et3NH)HC2O4 OR (Et3NH)2C2O4 AND SnPh3Cl: INFRARED STUDY - GORGUI AWA SECK; LIBASSE DIOP; ABOUBACARY SENE (Journal of Engineering Studies and Research)
Five new oxalato, hydrogenoxalato and hydrogenocarbonato adducts (three) and complexes (two) obtained on allowing (Et3NH)HC2O4 or (Et3NH)2C2O4 to react with SnPh3Cl have been studied by infrared spectroscopy, then discrete structures suggested on the basis of spectroscopic data. The anions behave as monochelating ligands, the environments around the metallic centres being octahedral. In two of the compounds, the benzene molecules obtained in situ are lattice. In all these structures when considering the cation involved in extra hydrogen bonds, a supramolecular architecture may be obtained.